Dental Perspective: Recognition and Response to Child Abuse and Neglect in Indian Setting - Shalu Rai; Mandeep Kaur; Sandeep Kaur (Wolters Kluwer Medknow Publications, 2011)
Child abuse is prevalent in every segment of society and is witnessed in all social, religious and professional strata. India has taken large strides in addressing issues, such as child education, health and development. However, in a country with a child population of around 440 million, child abuse and protection has remained largely unaddressed. Since most of the physical abuse injuries occur in orofacial region, dentists can easily diagnose them. While oral rare professionals may often recognize clinical symptoms suggesting child abuse, they may not always know their legal or ethical obligations to report their findings or suspicions. The intent of the article is to help dental care professionals more accurately identity and report child abuse and neglect with respect to the Indian scenario.